2011
DOI: 10.1002/pip.1025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of damp‐heat and UV aging tests on the optical properties of silicone and EVA encapsulants

Abstract: The absorption coefficient α(λ) of polydimethylsiloxane (PDMS) silicone and ethylene vinyl acetate (EVA) is monitored during exposure to damp‐heat (DH) and UV accelerated aging tests. In the DH test, the samples were exposed to 85% relative humidity at 85°C for 1325 h, satisfying the DH components of the IEC, UL, and IEEE's humidity‐freeze and DH tests. It is shown that moisture introduced by the DH exposure scatters incident light, reducing transmission through test samples and complicating optical experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 13 publications
1
53
0
Order By: Relevance
“…Two types of sensors with tin thicknesses of 70 and 160 nm were fabricated, together with the gold reference with a film thickness of 100 nm to control the intensity of incident light and compensate for optical disturbance and degradation due to glass and EVA. 10) Two types of sensors of different thicknesses are expected to indicate different quantities of acetic acid. The m AA values for the 70 and 160 nm sensors are calculated to be 52.5 and 120 µg, respectively.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of sensors with tin thicknesses of 70 and 160 nm were fabricated, together with the gold reference with a film thickness of 100 nm to control the intensity of incident light and compensate for optical disturbance and degradation due to glass and EVA. 10) Two types of sensors of different thicknesses are expected to indicate different quantities of acetic acid. The m AA values for the 70 and 160 nm sensors are calculated to be 52.5 and 120 µg, respectively.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…10) However, the relationship between the DH test and the real exposure test has not been completely understood, and precise determination of the acceleration coefficient of the DH test is still challenging. 8) Much effort has been dedicated to clarifying the degradation mechanism of a PV module during the DH test, 6,9,10) and recent studies have revealed that the production of acetic acid from the ethylene-vinyl acetate (EVA) copolymer encapsulant is one of the serious causes of degradation. 6,[11][12][13] The production pathway of acetic acid during the DH test is considered to be the hydrolysis of the EVA encapsulant by water from moisture penetrating into the back sheet of a PV module.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from deficiencies of the embedding material, like diffusion of water vapor [16] or yellowing of the EVA [17], one could expect an increase in series resistance of the cells due to abrasion or slow oxidation or other chemical reactions of the contact strips. This might go as far as complete loss of electrical contact between cells.…”
Section: Results Of Thermal Cycling Of Small Modulesmentioning
confidence: 99%
“…It also features very good self-priming adhesion and humidity resistance. More information on the advantages of using silicones over standard encapsulants such as EVA for PV modules can be found in [8]- [10], [15], and [16]. In short, the main advantages of silicones are transparency, expected improved reliability, and liquid processing possibilities.…”
Section: Materials and Fabrication Technologiesmentioning
confidence: 99%
“…Specifically for PV module packaging, where a high transparency of the front sheet and encapsulants throughout its functional life is required, the significant UV exposure to solar radiation can be detrimental to some polymer encapsulants. The so-called yellowing and browning of EVA is not an issue for silicones, as they are essentially UV-transparent and therefore inherently UV-stable [9], [11]. For PV modules, also heat (dissipation) issues are important, as a higher temperature negatively affects the cell performance.…”
mentioning
confidence: 99%